CHRONIC OSTEOMYELO-ARTHRITIS DUE TO BRUCELLA: A RARE CASE - DR ANITA PJAVALGI; DR VIJAYALAXMI S PATIL; DR DIVYA PURSNANI (International Journal of Pharma and Bio Sciences, 2015)
Human brucellosis alias Malta fever is a zoonotic infection caused by the genus brucellae. Osteomyelitis, spondylitis, sacroiliitis and peripheral arthritis are various osteoarticular presentations of brucellosis. Total complication risk is 1-35 percent. Osteomyelitis due to brucella is a rare entity in our population. A 54 year old male sought care in our orthopaedic opd with complaints of pain in right hip since one and half years. Pain was gradual in onset, dull aching, non-radiating and associated with reduced movement at hip joint. X-Ray and MRI findings showed destruction and erosions of right femoral head and acetabulum. Serological test were positive for Brucella antibodies. He underwent Girdle stone osteotomy and histopathological diagnosis of chronic osteomyelitis with avascular necrosis of head and neck of right femur due to Brucellosis was done .Brucellosis one of the neglected zoonotic disease, should be considered whenever there is a febrile illness with rheumatological complaints. Early recognition of the cause, appropriate antibiotic treatment, and regular long term follow up will improve the outcome of patients and lessen economic ramifications.